Пінський церковний собор 7–10 лютого 1942 р. та його наслідки - Смирнов, А. (Український історичний збірник, 2019)
Стаття присвячена Пінському Собору 1942 р. та його наслідкам для української православної спільноти. Митрополит Варшавський Діонісій Валединський призначив архієпископа Луцького Полікарпа Сікорського “тимчасовим адміністратором Православної Церкви на визволених українських землях”. У лютому 1942 р. у Пінську владика Полікарп за допомогою архієпископа Олександра Іноземцева розпочав рукоположення єпископів для української Церкви в канонічній єдності з Варшавським митрополитом. Нововисвячених архієреїв Юрія Кореністова, Ніканора Абрамовича та Ігоря Губу включили до складу Собору єпископів. Затверджений спеціальний чин приєднання липківських священиків через сповідь і прочитання формули рукопокладення на практиці єпископами УАПЦ реалізовувався як повторна хіротонія. Це рішення дало можливість залучити патріотичне духовенство до автокефального руху і поширити вплив Адміністратури на Схід України. Детально проаналізована реакція різних церковних середовищ на пінські ухвали. The article deals with the Pinsk Council, 1942 and its consequences for the Ukrainian Orthodox community. Following the German invasion of Ukraine efforts were immediately begun to revive the Church there. On December 24, 1942 Metropolitan Dionisii Valedynskyi of Warsaw appointed Polikarp Sikorskyi, the Archbishop of Lutsk, to the post of the ‘Temporary Administrator of the Orthodox Autocephalous Church in the liberated lands of Ukraine’ and also blessed Archbishops Polikarp and Olexander of Pinsk and Polissia to consecrate new bishops for Ukraine. On February 10, 1942, the Council of bishops meeting in Pinsk responded to the request of the surviving clergy and faithful of the UAOC’s 1921 formation by accepting them under jurisdiction of the Autocephalous Orthodox Church in Ukraine. During this historical meeting, Archimandrite Nikanor Abramovych (February 9) and Archimandrite Ihor Huba (February 10) were ordained by Archbishop Polikarp Sikorskyi, Archbishop Olexander Inozemtsev and Bishop Yurii Korenistov of Brest, who was himself consecrated on 8 February by Polikarp and Oleksander. The reaction of different ecclesiastical groups towards the Pinsk Council is studied in detail.